Staging America : The Artistic Legacy of the Provincetown Players - Kennedy, Jeffery, 1956- (Book collections on Project MUSE., 2023)
"A comprehensive history of the Provincetown Players and their influence on modern American theatre The Provincetown Players created a revolution in American theatre, making room for truly modern approaches to playwriting, stage production, and performance unlike anything that characterized the commercial theatre of the early twentieth century. In Staging America: The Artistic Legacy of the Provincetown Players, Jeffery Kennedy gives readers the unabridged story in a meticulously researched and comprehensive narrative that sheds new light on the history of the Provincetown Players. This study draws on many new sources that have only become available in the last three decades; this new material modifies, refutes, and enhances many aspects of previous studies. At the center of the study is an extensive account of the career of George Cram Cook, the Players' leader and artistic conscience, as well as one of the most significant facilitators of modernist writing in early twentieth-century American literature and theatre. It traces Cook's mission of "cultural patriotism," which drove him toward creating a uniquely American identity in theatre. Kennedy also focuses on the group of friends he calls the "Regulars," perhaps the most radical collection of minds in America at the time; they encouraged Cook to launch the Players in Provincetown in the summer of 1915 and instigated the move to New York City in fall 1916. Kennedy has paid particular attention to the many legends connected to the group (such as the "discovery" of Eugene O'Neill), and also adds to the biographical record of the Players' forty-seven playwrights, including Susan Glaspell, Neith Boyce, Edna St. Vincent Millay, Floyd Dell, Rita Wellman, Mike Gold, Djuna Barnes, and John Reed. Kennedy also examines other fascinating artistic, literary, and historical personalities who crossed the Players' paths, including Emma Goldman, Charles Demuth, Berenice Abbott, Sophie Treadwell, Theodore Dreiser, Claudette Colbert, and Charlie Chaplin. Kennedy highlights the revolutionary nature of those living in bohemian Greenwich Village who were at the heart of the Players and the America they were responding to in their plays. "--